Stacked microstrip patch antenna for high gain application - Norbahiah Misran; mohammad Tariqul islam; Farizah Ansarudin (Universiti Kebangsaan Malaysia, 2010)
A novel design technique for enhancing gain that improves the performance of a conventional microstrip patch antenna is proposed. This research addresses a novel wideband probe fed inverted stacked multiple slotted microstrip patch antenna. The design adopts contemporary techniques; probe feeding, inverted patch structure and stacked multiple slotted patch. The composite effect of integrating these techniques and by introducing the novel multiple shaped patch, offer a low profile, broadband, high gain and compact antenna element. The result showed satisfactory performance with maximum achievable gain of about 11.42 dBi. The design is suitable for array applications especially for base station.